Nanofiber‐Coated CF/PEEK Composite: Boosting Osteogenesis for Enhanced Bone Grafting - Dan‐Lei Yang; Louise A. Stephen; Junaid Ahmad Qayyum; Dongmin Yang; Colin Farquharson; Norbert Radacsi (Macromolecular Materials and Engineering)
Abstract This study presents the fabrication of carbon‐fiber‐reinforced polyetheretherketone (CF/PEEK) by 3D printing, which is subsequently coated with elastic nanofibers by electrospinning. CF/PEEK is an FDA‐approved implantable material possessing excellent mechanical properties similar to those of human cortical bone. As such, it is a prime candidate for replacing conventional metallic implants. However, it is limited by its bioinertness and inferior osteogenic properties. In this study, CF/PEEK is engineered to have improved hydrophilic properties and generated micro/nano‐topographical structures on its surface. This is achieved by electrospinning directly onto the 3D‐printed CF/PEEK with fibers incorporating hydroxyapatite particles and gelatin. The results show that the micro‐/nano‐topographical CF/PEEK demonstrates a significant increase in mineralizing potential compared to non‐coated implants, where no mineralized matrix is observed. These fiber coating modifications to CF/PEEK are a promising and important step forward in the improvement of in vivo implant‐bone osteointegration.